2D double aeolotropic conductive Janus pellicle with multi-functionality then derived 3D dual-wall Janus-type tube - H. N. Qi; Q. L. Ma; Y. R. Xie; Y. Song; J. Tian; W. S. Yu; X. T. Dong; D. Li; G. X. Liu; J. X. Wang (eXPRESS Polymer Letters)
Two-dimensional (2D) bilayer Janus pellicle (denoted as BJP) of concurrent double aeolotropic electrical conduction, superparamagnetism and luminescence is designed and constructed via electrospinning by using one-dimensional (1D) nanofibers and Janus nanoribbons as constructive units. The BJP comprises top-down two layers tightly bonded together. The top layer is a left-right structured Janus film which consists of Janus nanoribbons array as left and right side, and further, arrangement orientations of Janus nanoribbons in the two sides are perpendicular, leading to double aeolotropic conduction, and the conduction ratio reaches 108 times. The down layer is a non-array luminescent film made of nanofibers. Under the excitation by 291 and 294 nm light, red luminescence of the left side of the top layer and green luminescence of down layer in BJP are respectively achieved. The maximum saturation magnetization of the top layer can reach 21.45 (emu/g). By rolling the 2D BJP into the tube respectively with the ways of rolling from left to right or from up to down, three-dimensional (3D) dual-wall Janus-type tube with the Janus-type tube as outer or inner and the homogeneous tube as inner or outer is obtained.